2021
DOI: 10.5194/ms-12-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic synthesis method and eccentricity effects of a Stephenson mechanism

Abstract: Abstract. When implementing the technological process on crank presses, it is necessary to provide a predetermined working cycle of the slider motion: fast lifting, dwell, and slow lowering. The cycle cannot be realized without controlling the motor. In addition, using controllable motors increases the manufacturing cost. Due to the geometric and kinematic capabilities of the mechanism, changing the kinematics of the working link is the best choice. Thanks to the use of the Stephenson II mechanism, the slider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Kinematic (e.g., [20] and [21]), kinetostatic (e.g., [22]) and dynamic analysis (e.g., [23] and [24]), synthesis studies (e.g., [20] and [25]) and different optimization types and techniques (e.g., [26] to [28]) were carried out for the inversor mechanisms. For example, a numerical method based on the meansquare minimization of the objective function [29] can be used for the kinematic synthesis of the Stephenson mechanism. Other modern methods can also be used to optimize these planar mechanisms (e.g., the genetic algorithm, approached in [28]).…”
Section: Introductionmentioning
confidence: 99%
“…Kinematic (e.g., [20] and [21]), kinetostatic (e.g., [22]) and dynamic analysis (e.g., [23] and [24]), synthesis studies (e.g., [20] and [25]) and different optimization types and techniques (e.g., [26] to [28]) were carried out for the inversor mechanisms. For example, a numerical method based on the meansquare minimization of the objective function [29] can be used for the kinematic synthesis of the Stephenson mechanism. Other modern methods can also be used to optimize these planar mechanisms (e.g., the genetic algorithm, approached in [28]).…”
Section: Introductionmentioning
confidence: 99%
“…In the works [11,12] a crank-slide double-rod mechanism of Stephenson II is proposed, which, in comparison with the existing operating mechanism of the crank press, has broader functionality. The structure of such mechanisms makes it possible to realize the exact working link dwell [13].…”
Section: Introduction and Review Of Sourcesmentioning
confidence: 99%
“…In order to better characterize its structural features, it is called Crank-Triangular Linkage-Elbow mechanism (CTLE) in this paper. CTLE has attracted extensive attention from researchers and manufacturers of servo presses owing to its good kinematic and dynamic characteristics [4,5,[9][10][11][12]. Especially, CTLE has a high mechanical advantage and low and steady speed in S n , meeting the requirements for mechanical servo press [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that eccentricity of Stephenson mechanism affects the lower forward and higher backward speed of the slider. The literature only provides numerical analysis of kinematics, lacking dynamic analysis [10]. In summary, the general approach to solve the optimization problem of planar linkage system is:…”
Section: Introductionmentioning
confidence: 99%